Changes in Human Erythrocyte Membrane Exposed to Aqueous and Ethanolic Extracts from Uncaria tomentosa - Piotr Duchnowicz; Radosław Pilarski; Jaromir Michałowicz; Bożena Bukowska (Molecules, 2021)
Uncaria tomentosa (Willd.) DC is a woody climber species originating from South and Central America that has been used in the therapy of asthma, rheumatism, hypertension, and blood purification. Our previous study showed that U. tomentosa extracts altered human erythrocyte shape, which could be due to incorporation of the compounds contained in extracts into the erythrocyte membrane. The aim of the present study was to determine how the compounds contained in U. tomentosa extracts incorporate into the human erythrocyte membrane. The study has assessed the effect of aqueous and ethanolic extracts from leaves and bark of U. tomentosa on the osmotic resistance of the human erythrocyte, the viscosity of erythrocyte interior, and the fluidity of erythrocyte plasma membrane. Human erythrocytes were incubated with the studied extracts in the concentrations of 100, 250, and 500 µg/mL for 2, 5, and 24 h. All extracts tested caused a decrease in erythrocyte membrane fluidity and increased erythrocyte osmotic sensitivity. The ethanolic extracts from the bark and leaves increased viscosity of the erythrocytes. The largest changes in the studied parameters were observed in the cells incubated with bark ethanolic extract. We consider that the compounds from U. tomentosa extracts mainly build into the outer, hydrophilic monolayer of the erythrocyte membrane, thus protecting the erythrocytes against the adverse effects of oxidative stress.